A Market Assessment of Distributed Battery Energy Storage to Facilitate Higher Renewable Penetration in an Isolated Power System - Neil McIlwaine; Aoife M. Foley; Dlzar Al Kez; Robert Best; Xi Lu; Chongyu Zhang (IEEE Access, 2022)
Power systems with a high share of renewables require additional ancillary services to operate safely and reliably. System operators are introducing schemes to attract investment in technology which will provide ancillary services. Battery storage can provide some of these services but investment in equipment is required. This study investigates the potential benefits of energy storage and tests the market arrangements to attract investment. The study uses a combination of numerical and system analyses to test the financial performance. A dynamic economic dispatch model was used to evaluate the system costs and emission levels. A unit commitment model was used to measure the reserve cost. Both models use real-time load data for a region in the Irish electricity market. The ancillary service revenue is modelled based on actual renewable levels for the Irish system. The frequency and rate of change of frequency response are evaluated by introducing a disturbance to the system model with and without energy storage. The results were used to test investment opportunities using established financial appraisal techniques.